2020
DOI: 10.3390/diagnostics10121095
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Metabolic Profile of Patients with Lung Cancer, Chronic Obstructive Pulmonary Disease of Varying Severity and Their Comorbidity: A Preliminary Study

Abstract: The aim of the work was to study the features of the salivary biochemical composition in the combined pathology of lung cancer and chronic obstructive pulmonary disease (COPD) of varying severity (COPD I, COPD II). The study group included patients with lung cancer (n = 392), non-malignant lung pathologies (n = 168) and healthy volunteers (n = 500). Before treatment, the salivary biochemical composition was determined according to 34 indicators. Survival analysis performed by the Kaplan-Meier method. Biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…As the degree of damage to the lymph node lesion rises, the level of imidazole compounds also increases. Thus, the level of imidazole compounds in saliva can be used as an important biomarker for lung cancer detection. , …”
Section: Resultsmentioning
confidence: 99%
“…As the degree of damage to the lymph node lesion rises, the level of imidazole compounds also increases. Thus, the level of imidazole compounds in saliva can be used as an important biomarker for lung cancer detection. , …”
Section: Resultsmentioning
confidence: 99%
“…In this study, we examined groups of patients without COPD, with mild and moderate COPD (GOLD I, GOLD II), designated, respectively, NO COPD, COPD I and COPD II. Additional division of these into subgroups in accordance with the histological type of lung cancer was not carried out since we have previously shown that the factor of the presence/absence of COPD is more significant for changes in the metabolic profile of saliva than the histological type of lung cancer [ 29 ]. All patients with COPD were out of the exacerbation stage, and therefore non-drug support measures were implemented and short-acting bronchodilators were prescribed for use as needed.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we identified 34 biochemical parameters of saliva, which statistically significantly change in lung cancer of various histological types in comparison with healthy controls [ 17 ]. We have previously shown that the presence of COPD as a concomitant pathology does not fundamentally change the metabolic profile of saliva but increases the range of changes in the corresponding biochemical indicators [ 29 ]. Biochemical indicators (catalase, imidazole compounds, sialic acids, lactate dehydrogenase) have been identified, which can be used to monitor patients from risk groups for the timely diagnosis of lung cancer, in particular patients with early stages of COPD [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation